Violence against children: challenges for doctors alone to take? - Priszkulnik, Léia (O Mundo da Saúde, 2009)
This article approaches violence against children and the challenges these cases are as regards assistance, challenges that, necessarily, doctors can not take alone. According to WHO, violence must be considered a question of health as it is a threat to life. It is a worldwide phenomenon that reaches all social classes, is present in all countries and affects even children. If violence must be taken as a health question, not only doctors, but also psychoanalysts who work in the health area may be qualified to deal with it. Violence against children was considered for a long time something natural and normal by parents, doctors, Law etc. (Mary Ellen’s case). In the Twentieth century, the situation changes with the discovery, honoring, defense and protection of children (ONU and the Rights of Children and ECA in Brazil). Delgado, an official of the Health department, says that violence is one of the main factors of aggravation of health conditions in the population, being one of the challenges for public health. The work in the extended public network is being developed by multiprofessional teams. Psychoanalysts can help people affected by all forms of violence, opening a space for subjects to speak, for speaking has therapeutic effects and, as said Freud more than a time the objective of psychoanalysis is to reduce human suffering. These challenges are not only for doctors to take, and psychoanalysts can be part of multiprofessional teams.